Dampak Job Involvement Dalam Peningkatan Kinerja Pegawai Melalui Komitmen Organisasional (Studi Pada Kantor Badan Perencanaan Pembangunan Daerah Provinsi Daerah Istimewa Yogyakarta) - Fariha Azzahra; Tri Maryati (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2016)
This research aims to analyze the influence of job involvement toward job performance through organizational commitment in BAPPEDA (Badan Perencanaan Pembangunan Daerah) of Daerah Istimewa Yogyakarta. The subject in this study was all employees at BAPPEDA DIY. In this research, the sample of 102 respondents was selected using census technique. Analysis tool used in this research is SEM (Structural Equation Modeling).Based on the analysis, the results were the job involvement is positif and significant to the job performance and organizational commitment does not infuence significantly to the job performance. Moreover,organizational commitment is not mediated the relationship between job involvement and job performance.